The Aesthetics of Sand Beds in Kampung Kasur Pasir, East Legung Village, Sumenep, Madura - Maharlika, Febry (Universitas Pasundan, 2025)
This study examines the aesthetic value of sand beds in Kampung Kasur Pasir,East Legung Village, Sumenep, Madura, by comparing the aesthetic perspectives of the Western and Eastern worlds. Sand beds are a unique cultural phenomenon that blends natural elements with local traditions, creating a rich aesthetic experience for the local community. From a Western perspective, the aesthetics of sand beds can be analyzed through the concept of visual harmony in both form and content. Meanwhile, from an Eastern perspective, sand beds represent spiritual balance and a harmonious relationship between humans, nature, and the Creator. The findings reveal that sand beds serve not only as a place for rest but also as a medium of aesthetic expression that integrates cultural, emotional, and spiritual elements. This multidisciplinary approach highlights how local aesthetic values can contribute significantly to the global understanding of aesthetics. This study aims to enrich the discourse on beauty within the context of local traditions while offering new insights into the interaction between culture and aesthetics from diverse perspectives.